2023
DOI: 10.1055/a-2031-0874
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection techniques and technology: European Society of Gastrointestinal Endoscopy (ESGE) Technical Review

Abstract: ESGE suggests conventional endoscopic submucosal dissection (ESD; marking and mucosal incision followed by circumferential incision and stepwise submucosal dissection) for most esophageal and gastric lesions. ESGE suggests tunneling ESD for esophageal lesions involving more than two-thirds of the esophageal circumference. ESGE recommends the pocket-creation method for colorectal ESD, at least if traction devices are not used. The use of dedicated ESD knives with size adequate to the location/thickness of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 259 publications
(312 reference statements)
2
31
0
5
Order By: Relevance
“…Excluding the patients whose lesions were advanced cancer (n = 7), there were also patients with early esophageal cancer (n = 10), HGIN (n = 10), HGIN (n = 2), and LGIN (n = 17) who declined endoscopic or surgical interventions, preferring more intensive monitoring instead. Previous studies have shown a certain proportion of patients with early esophageal cancer or HGIN whose preoperative histopathology usually suggested esophageal LGIN (24). Therefore, endoscopic biopsies can result in the underestimation and misjudgment of esophageal lesions in the absence of postoperative pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Excluding the patients whose lesions were advanced cancer (n = 7), there were also patients with early esophageal cancer (n = 10), HGIN (n = 10), HGIN (n = 2), and LGIN (n = 17) who declined endoscopic or surgical interventions, preferring more intensive monitoring instead. Previous studies have shown a certain proportion of patients with early esophageal cancer or HGIN whose preoperative histopathology usually suggested esophageal LGIN (24). Therefore, endoscopic biopsies can result in the underestimation and misjudgment of esophageal lesions in the absence of postoperative pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Although endoscopic intermuscular dissection (EID) has been used successfully to treat rectal pathology [1], its application in stomach procedures has not been reported. EID involves the dissection of the circular layer from the longitudinal layer of the muscularis propria to achieve a clear vertical dissection margin [2,3]. A 43-year-old woman was referred to our center for endoscopic resection of a 15-mm type 1 neuroendocrine tumor (NET) located in the lower gastric body (▶ Fig.…”
Section: First Report Of Gastric Endoscopic Intermuscular Dissectionmentioning
confidence: 99%
“…In order to manage lesions with severe submucosal fibrosis, we have developed the pocket-creation method (PCM) [5] [6]. PCM is one of the techniques recommended for colorectal ESD in the 2023 technical review from the European Society of Gastrointestinal Endoscopy (ESGE) [7]. However, during the pocket-opening process, the surrounding mucosa gradually loses traction, and the lesion becomes very 5 magnifying endoscopic findings and magnifying endoscopic findings using Japan Narrow Band Imaging Expert Team (JNET) classification [11] and/or Kudo's pit pattern [12].…”
Section: Introductionmentioning
confidence: 99%